A Longitudinal Study of Changes in Cognition Among Older Thais: Studying From the Kanchanaburi Demographic Surveillance System. (July 2019) - Auampradit, Natchaphon; Vapattanawong, Patama; Punpuing, Sureeporn; Sunpuwan, Malee; Jirapramukpitak, Tawanchai
Objectives: To examine the impacts of changes in social determinants of health (SDH) toward changes in cognition.Methods: Longitudinal data came from the Kanchanaburi Demographic Surveillance System (KDSS) collected in 2007 and 2011. Cognitive impairment was measured by category fluency and delayed recall. Generalized estimating equation (GEE) was used to investigate changes in cognition by taking SDH and other variables including age, gender, marital status, education, and depression into the model.Results: GEE revealed longitudinal effects of wealth index and working status against cognition. Older Thais living with richest wealth index (odds ratio [OR] = 0.54; 95% confidence interval [CI] = 0.31-0.94) and still being employed (OR = 0.65; 95% CI = 0.47-0.89) were less likely to have cognitive impairment.Discussion: Poorer wealth index and being unemployed were served as a risk factor for cognitive impairment over time. Increasing age was still the major risk for cognitive impairment.